Null objects in the spontaneous speech of monolingual and bilingual speakers of European Portuguese - Rinke, Esther (2017)
This paper investigates object omissions in the spontaneous production of European Portuguese by second generation Portuguese-German bilingual speakers and compares them to first generation migrants, and two age-matched groups of monolingual speakers. The results show that bilingual speakers as well as the younger generation of monolinguals show a higher number of null objects in their speech than the two older generations. This may reflect an inter-generational development that favours null objects, which is independent of language contact. The analysis of the syntactic and semantic conditions determining the occurrence of null objects in the speech of the different groups reveals that the semantic properties of the null objects realized by the bilinguals, particularly the higher rates of animate and nonpropositional null objects, show that they extend the semantic-pragmatic conditions of null object realization along the referentiality hierarchy proposed by Cyrino, Duarte and Kato (2000). The bilingual speakers may reflect a language-internal pathway that appears to resemble a diachronic change observed in BP.